Effect of high hydrostatic pressure on the quality of red raspberry wine. Issue 9 (28th October 2021) - Cao, Zhixiang; Li, Yuxin; Yu, Chenchen; Li, Shengyun; Zhang, Xuemei; Tian, Yiling
Abstract: In order to explore the influence of high hydrostatic pressure (HHP) on the quality of red raspberry wine, HHP technology was used to hold the red raspberry wine under the conditions of 200–600 MPa for 5 min/20℃, compared with the red raspberry wine without HHP treatment. Then the changes in aroma components, ellagic acid content, alcohol content, colony‐forming unit and sensory quality of red raspberry wine under different HHP conditions were evaluated. The results showed that HHP affected the aroma components of red raspberry wine. Principal component analysis showed that HHP treatment greatly affected the characteristic constituents of alcohols and esters. Simultaneously, it changed the content and composition of phenolic substances in red raspberry wine. For example, ellagic acid content was 35.15 mg/L at 400 MPa, which was 3 times higher than of normal pressure. No significant difference was found about the alcohol content of the wine subjected to HHP treatment within 400 MPa. However, the alcohol content decreased if it was higher than 400 MPa. In addition, HHP technology could eliminate the microorganisms. This research provides theoretical foundation for the HHP technology usage to red raspberry wine. Novelty Impact Statement: There are three main contributions from this research. Firstly, High hydrostatic pressure (HHP) has greater impact on the aroma of red raspberry wine with alcohols and esters. Secondly, HHP technology could increase the content of phenolic substances in red raspberry wine, while the compositions were also changed. More importantly, the content of ellagic acid that could inhibition of cancer were improved under HHP treatment conditions with 400 MPa in red raspberry wine, and the content of alcohol were reduced at the same time.